STUDENTS WITH HIGH FUNCTIONING AUTISM (HFA) AND GIFTEDNESS (2E); DO THEY FEEL BORED IN SCHOOL? - Aziz, Ilyah Abd (PUPIL: International Journal of Teaching, Education and Learning, 2020)
High Functioning Autism (HFA) students that are gifted, either in academics or talents are always looking for new stimulating challenges when learning and at times are perceived as geniuses. They are categorized as 2E or known as twice-exceptional, where they are gifted but at the same time, they have learning issues challenging them. They do not face a lot of problems when learning in classes on the subject they like and are interested in but eventually have challenges when it comes to subjects that do not interest them. They are often easily bored if there are too many repetitions of learning or they are already well advanced in a subject and could be disruptive, in cases, which lead to others thinking that they have behavioral problems and severe learning disabilities. Their emotions also will be disruptive if they get bored and learning and focus will decline. They often have an interest or obsession towards a subject, making them way ahead knowledgeable than their peers their age in the subject. The research is aimed at finding if a lot of HFA/2E gifted students face boredom in school, be it government, international, or learning centers. Surveys were given out to 50 families with HFA students and additional interviews were done to 4 families. Hopefully, with the findings and suggestions, it could help the HFA/2E students to excel and contribute more in the future while controlling their emotions and needs that usually is triggered by boredom. The support needed is not mainly from the school itself but also from family members and the need to have friends around.